Chinese Peking Opera Elements in Zhang Zhao's Piano Work Pi Huang - Shaozheng, Chen; Tajuddin, Tazul (Journal of Ecohumanism, 2024)
Peking opera is a representative type of traditional Chinese opera. It originated during the reign of Emperor Qianlong of the Qing Dynasty. It incorporates elements of various operas such as Hui opera and Han opera. It is famous for its unique singing style, facial makeup, and costumes. It is performed by singing, reciting, acting, and fighting. There are two main operatic tune Peking opera, Xipi and Erhuang. The musical accompaniment mainly uses Jinghu, Jingerhu (traditional Chinese stringed instrument) and percussion instruments. As an important symbol of Chinese culture, Peking opera has been listed as an intangible cultural heritage of the United Nations. Pi Huang is a solo piano work composed by Chinese composer Zhang Zhao using the elements of Chinese Peking Opera, which involves the use of the Structure of Banqiang and vocal elements of Peking Opera. The piece imitates the timbre and technique of the accompaniment instruments of Peking Opera, which is also one of Zhang Zhao's most representative works. This paper analyzes the background, structure, and characteristics of the piano piece Pi Huang, and reveals the profound meaning and connotation of the work, to provide a valuable reference for performers and teaching research.